2016
DOI: 10.1016/j.bbrc.2016.02.065
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 inhibits hyperglycemia-induced pyroptosis in human ventricular cardiomyocytes by targeting ELAVL1

Abstract: Diabetic cardiomyopathy is a common complication in patients with diabetes and is associated with underlying chronic inflammation and cardiac cell death, subsequently leading to heart failure (HF). ELAV-like protein 1 (ELAVL1) plays a critical role in the progression of inflammation and HF. However the role of ELAVL-1 in inflammation induced cardiac cell death (pyroptosis) under hyper glycemic condition remains elusive. Our data demonstrates that ELAVL1 expression augmented with a concomitant increase in caspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 33 publications
4
115
0
Order By: Relevance
“…Therefore, caspase-1 dependence is a definitive feature of pyroptosis that is characterized by the release of pro-inflammatory contents and plasma membrane rupture. Recent studies have demonstrated that pyroptosis mediated the death of renal and cardiac cells, leading to kidney and heart failure [11, 12, 43]. Our findings were consistent with those previously reported results.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, caspase-1 dependence is a definitive feature of pyroptosis that is characterized by the release of pro-inflammatory contents and plasma membrane rupture. Recent studies have demonstrated that pyroptosis mediated the death of renal and cardiac cells, leading to kidney and heart failure [11, 12, 43]. Our findings were consistent with those previously reported results.…”
Section: Discussionsupporting
confidence: 94%
“…MiR-9 has been reported to play important roles in inflammatory response [36], immune regulation [36], lipid uptake [38], neuron differentiation [39], and many kinds of tumors [40]. Our results indicate potential anti-inflammatory effects and inhibition of NLRP3 inflammasome by mir-9.…”
Section: Discussionmentioning
confidence: 52%
“…Through regulating its target gene ELAVL1 , mir-9 inhibited hyperglycemia-induced pyroptosis (cardiac cell death) in human ventricular cardiomyocytes. ELAVL1 knockdown abrogates TNF-α induced canonical pyroptosis via NLRP3, caspase-1 and IL-1β suppression[40]. Over-expression of miR-9 in isolated human chondrocytes reduced IL-1β-induced TNF-α production and inhibited MMP-13 in human chondrocytes[41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-11 can trigger pyroptosis, but its effects on IL-1β and IL-18 maturation are indirect, because this process requires the NLRP3-dependent activation of caspase-1 [26,27]. Pyroptosis induces pathological inflammation, which is involved in the pathogenesis of multiple inflammatory diseases in several organs, including bowel [28], brain [29], heart [30] and kidney [31]. In gastritis, inflammation and mucosal cell death are also present.…”
Section: Introductionmentioning
confidence: 99%